Usulan Peningkatan Kinerja Mesin CNC Bubut Menggunakan Metode Overall Equipment Effecetiveness (OEE) DI PT STSS - KENJI, RESKY KUMAKURA; KURNIAWAN, DWI (e-Proceeding FTI, 2024)
The development of the industrial world is increasing so that good production processes are needed. The high productivity capabilities of machines have an impact on the efficiency of production costs and selling prices. PT. STSS is a manufacturing company that produces various kinds of machine spare parts. One of the machines in operation, namely the CNC lathe, often experiences downtime conditions so that the use of the machine is less effective which results in production targets not being achieved. It is necessary to identify the productivity level of a machine using the Overall Equipment Effectiveness (OEE) method todetermine losses that arise during the production process. taking place. Therefore, it causes high values of reduce speed losses and idle and minor stoppage losses which are caused by the lack of repair capabilities, equipment storage methods that are not well organized, machines topping momentarily and materials that do not meet specifications. and provide suggestions for improving the work performance of CNC lathe machines so that the Overall Equipment Effectiveness (OEE) assessment results are 67%. Abstrak Perkembangan dunia industri semakin meningkat sehingga diperlukan proses produksi yang baik. Kemampuan produktivitas mesin yang tinggi berdampak pada efisiensi biaya produksi dan harga jual. PT. STSS merupakan perusahaan manufaktur yang memproduksi berbagai macam sparepart mesin. Salah satu mesin yang beroperasi yaitu mesin CNC bubut sering mengalami kondisi downtime sehingga penggunaan mesin yang kurang efektif yang diakibatkan target produksi tidak tercapai maka perlu mengidentifikasikan tingkat produktivitas dari mesin menggunakan metode Overall Equipment Effectiveness (OEE) untuk mengetahui kerugian yang muncul pada saat proses produksi berlangsung. Oleh karena itu menyebabkan tingginya nilai reduce speed losses dan iddle and minor stoppage losses yang disebabkan oleh minimnya kemampuan perbaikan, cara penyimpanan alat yang tidak terorganisir dengan baik, mesin terhenti sesaat dan material yang tidak sesuai spesifikasi. dan memberikan usulan peningkatan kinerja kerja mesin CNC bubut sehingga hasil penilaian Overall Equipment Effectiveness (OEE) yaitu 67%.